Arrested development: a daughter's autoethnographic exploration of paternal incarceration - Roden, Kayla (The University of Edinburgh, 2025)
In the United States, millions of children currently have an incarcerated parent, with millions more having past experiences of paternal incarceration at some point during their lives (Kjellstrand and Eddy, 2011b). My research offers entry into the often hidden, isolated and fragmented world of children with imprisoned fathers. Historically, research on children with incarcerated parents has been limited, resulting in them being deemed an ‘invisible’ population (McDonald, 2009). More recent research on children with incarcerated parents has tended to be quantitative or take a clinical focus, tending to present such children as ‘victims’ at risk of a variety of adverse childhood outcomes. Few studies utilise the voices of children themselves to understand this phenomenon. Employing an autoethnographic approach, this thesis provides insights into the thoughts, feelings and experiences of a child who has a father in prison and how this experience impacts their sense of identity as they grow into adulthood. Stigma and shame emerge as powerful organising themes, and the life course approach demonstrates how the experience continues to influence, even construct, the adult-child experience long after their father is released. The author invites the reader to journey with them through truthful, playful, creative and evocative renderings of memories and experiences spanning childhood into adulthood and past into present. As a storyteller and researcher, the author engages in dialogue with relevant literature to learn more about this population and to develop their own unique contribution to this field of study. Paramount in this is the inclusion of the voices of other children with incarcerated parents, with a central place given to the small body of relevant literature that utilises their voices as research data. My hope is that this research can be used by professionals to help them better understand this ‘invisible’ population so that support services and research in the future will better aim to hear and capture their voices and respond more effectively to the needs of this group. As importantly, I hope that adult children with experience of paternal incarceration will find their experience acknowledged and affirmed in this thesis.
Keywords: children with imprisoned parents; autoethnography; stigma; shame